Leukemic conversion involving RAS mutations of type 1 CALR-mutated primary myelofibrosis in a patient treated for HCV cirrhosis: a case report - Gurban, Petruta; Mambet, Cristina; Botezatu, Anca; Necula, Laura G.; Neagu, Ana I.; Matei, Lilia; Pitica, Ioana M.; Nedeianu, Saviana; Chivu-Economescu, Mihaela; Bleotu, Coralia; Ataman, Marius; Mocanu, Gabriela; et al. (Frontiers in Oncology, 2023)
Somatic frameshift mutations in exon 9 of the calreticulin (CALR) gene are recognized as disease drivers in primary myelofibrosis (PMF), one of the three classical Philadelphia-negative myeloproliferative neoplasms. Type 1/type 1-like CALR mutations particularly confer a favorable prognostic and survival advantage in PMF patients. We report an unusual case of PMF incidentally diagnosed in a 68-year-old woman known with hepatitis C virus (HCV) cirrhosis who developed a progressive painful splenomegaly, without anomalies in blood cell counts. While harboring a type 1 CALR mutation the patient underwent a leukemic transformation in less than one year from diagnosis, with a lethal outcome. Analysis of paired DNA samples from chronic and leukemic phases by a targeted next-generation sequencing (NGS) panel and SNP microarray revealed that the leukemic clone developed from the CALR-mutated clone, through the acquisition of genetic events in the RAS signaling pathway: an increased variant allele frequency of the germline NRAS Y64D mutation present in the chronic phase (via an acquired uniparental disomy of chromosome 1) and gaining NRAS G12D in the blast phase. SNP microarray analysis showed five clinically significant copy number losses at regions 7q22. 1, Xp11.4, revealing a complex karyotype already in the chronic phase. We discuss how additional mutations, detected by NGS, as well as HCV infection and antiviral therapy, might have negatively impacted this type 1 2 This is a provisional file, not the final typeset article CALR-mutated PMF. We suggest that larger studies are required to determine if more careful monitoring would be needed in MPN patients also carrying HCV and receiving anti-HCV treatment.